Employing traffic lights as road side units for road safety information broadcasts - Alves, Luis Nero (2012)
There is great concern over growing road accidents and associated fatalities. In order to reduce accidents, improve congestion and offer smooth flow of traffic, several measures such as providing intelligence to transport, providing communication infrastructure along the road, vehicular communication and likewise are being undertaken. Traffic safety information broadcast from traffic lights using visible light communication (VLC) is a new cost effective technology which assists drivers to take necessary safety measures. This chapter presents VLC broadcast system considering LED-based traffic light. It discusses the integration of traffic light road side unit (RSUs) with upcoming intelligent transportation systems (ITS) architecture. Some of the offered services using this technology in vehicular environment together with future direction and challenges are discussed. A prototype demonstrator of the designed VLC systems is also presented.